Exponential Convergence for Cellular Neural Networks with Time-Varying Delays in the Leakage Terms. (1st November 2012) - Chen, Zhibin; Meng, Junxia
Abstract : We consider a class of cellular neural networks with time-varying delays in the leakage terms. By applying Lyapunov functional method and differential inequality techniques, we establish new results to ensure that all solutions of the networks converge exponentially to zero point.